Penerapan Tilang Elektronik dalam Penindakan Pelanggaran Lalu Lintas : Studi Kasus Satlantas Polda Metrojaya - Pardiana, Deni (Varied Knowledge Journal, 2023)
In the criminal justice system as stipulated in Law No. 16 of 2004 concerning the Indonesian prosecutor's office that the position of the prosecutor's office is decisive because the prosecutor's office is the link between the investigation stage and the examination stage in court until the decision is implemented. The execution authority in question is one of the policies mandated to the Attorney General's Office which has the role of executor. The collection of ticket fines and court costs has been regulated in the authority related to this matter, although its implementation in the field turns out to overlap with the authority exercised by the police. Based on the results of the research conducted, the following conclusions are obtained: 1) The Prosecutor's Office has the authority as the executor of court decisions that have permanent legal force to carry out the executorial function. Ticket fines as one of the Non-Tax State Revenues (PNPB), 2) the problems that occur in the process of executing ticket fines are incomplete identities in the record of evidence of traffic violations, ii then make it difficult for the Prosecutor's Office if the defendant does not attend the trial, the external obstacles faced in the form of PP No. 50 of 2010 concerning Police PNBP which has exceeded the provisions stipulated in Law No. 20 of 1997 concerning PNBP and the 2nd appendix to PP No. 22 of 1997 concerning Prosecutor's PNBP.